A Correlation Between Access To Information And Early Detection Behavior Of Cervical Cancer By Visual Inspection Of Acetic Acid (IVA) Method At Watas Marga Health Center In 2024 - Saragih, Sri Hartaty; Nurjanah, Nimas Ayu Lestari; Rossita, Taufanie (Universitas Dehasen Bengkulu, 2025)
IVA Test method is one of the effective and efficient methods for early detection of cervical cancer, apart from the low cost it can also be done by midwives or health center officers. The percentage of cervical cancer early detection examination (IVA) coverage in Indonesia is far from ideal coverage. Information on early detection of cervical cancer is needed by WUS to know the importance of early detection of IVA test. The purpose of the study is to determine a correlation between access to information and early detection behavior of cervical cancer by Visual Inspection of Acetic Acid (VIA) method at Watas Marga Health Center in 2024. This research is a type of quantitative research. The research design used is an analytical survey method with a cross sectional approach, this research was conducted at Watas Marga Health Center Work Area with a sample of 64 Women of Fertile Age (WUS). The results of this study there is a correlation between access to information with early detection behavior of cervical cancer with IVA test. From the results of bivariate analysis obtained OR value = 8.533 which means that respondents who are less good at obtaining information about early detection of cervical cancer have a chance of 8.533 times not to do early detection of cervical cancer with VIA test. Health Center is expected to further improve counseling to WUS about cervical cancer, this counseling is a way to provide information and knowledge to WUS.